A high figure of merit localized surface plasmon sensor based on a gold nanograting on the top of a gold planar film - 张祖银 王立娜 胡海峰 李康文 马勋鹏 宋国峰 (Chinese physics B, 2013)
We investigate the sensitivity and figure of merit （FOM） of a localized surface plasmon （LSP） sensor with gold nanograting on the top of planar metallic film. The sensitivity of the localized surface plasmon sensor is 317 nm/RIU, and the FOM is predicted to be above 8, which is very high for a localized surface plasmon sensor. By employing the rigorous coupled-wave analysis （RCWA） method, we analyze the distribution of the magnetic field and find that the sensing property of our proposed system is attributed to the interactions between the localized surface plasmon around the gold nanostrips and the surface plasmon polarition on the surface of the gold planar metallic film. These findings are important for developing high FOM localized surface plasmon sensors.